1992
DOI: 10.1002/pro.5560011207
|View full text |Cite
|
Sign up to set email alerts
|

A 1H NMR study of a ternary peptide complex that mimics the interaction between troponin C and troponin I

Abstract: The troponin I peptide Na-acetyl TnI Abbreviations: s-TnC, skeletal troponin C; TnI, troponin I; TnT, troponin T; CaM, calmodulin; SCIII, Ac-(AlOl) (Y112) s-TnC (93-126) amide; SCIV, Ac-s-TnC (129-162) amide; TnIp, Na-acetyl TnI (104-115) amide; TR2C, C-terminal domain (residues 92-162) of s-TnC; NOE, nuclear Overhauser enhancement; TRNOE, transferred nuclear Overhauser enhancement; 2D NOESY, two-dimensional nuclear Overhauser enhancement spectroscopy; 2D DQF-COSY, two-dimensional double-quantum filtered corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 61 publications
2
11
0
Order By: Relevance
“…4; Kinemages 1, 2). This result corresponds to the previous observation based on ' H chemical shift changes, that sTnIp, an inhibitory peptide corresponding to Gly 104-Arg 115 of sTnI, interacts with Phe and Ile residues in the C-terminal hydrophobic pocket of sTnC (Cachia et al, 1983;Slupsky et al, 1992). Alternatively, binding of cTnIp to a site other than the C-terminal hydrophobic pocket could result in a conformational change that leads to a decrease in solvent exposure for both Met residues 120 and 157.…”
Section: Discussionsupporting
confidence: 90%
“…4; Kinemages 1, 2). This result corresponds to the previous observation based on ' H chemical shift changes, that sTnIp, an inhibitory peptide corresponding to Gly 104-Arg 115 of sTnI, interacts with Phe and Ile residues in the C-terminal hydrophobic pocket of sTnC (Cachia et al, 1983;Slupsky et al, 1992). Alternatively, binding of cTnIp to a site other than the C-terminal hydrophobic pocket could result in a conformational change that leads to a decrease in solvent exposure for both Met residues 120 and 157.…”
Section: Discussionsupporting
confidence: 90%
“…The proposal that residues 116 to 131 of TnI binds the N domain of TnC further supports the binding of the inhibitory region along the central helix and into the C domain (Cachia et al, 1983(Cachia et al, , 1986Chandra et al, 1994;Dalgarno et al, 1982;Drabikowski et al, 1985;Grabarek et al, 1981;Howarth et al, 1995;Jha et al, 1996;Kobayashi et al, 1994, Krudy et al, 1994Lan et al, 1989;Leszyk et al, 1987Leszyk et al, , 1988Ngai et al, 1994;Slupsky et al, 1992;Swenson & Fredricksen, 1992;Tsuda et al, 1992;Wang et al, 1990;Weeks & Perry, 1978). Grabarek et al (1981), using a variety of proteolytic fragments of TnC, have indicated that the region comprising residues 89 to 100 of the central helix constitutes one of the two Ca 2 -dependent sites of interaction between TnI and TnC, based on the observations that only TnC fragments containing these residues are able to regulate the actomyosin ATPase activity when complexed with TnI and TnT, presumably by binding to the inhibitory region of TnI in the presence of calcium.…”
Section: Binding Of the Inhibitory Region To The Central Helix And C mentioning
confidence: 72%
“…Furthermore, the fact that the release curves for peptides TnI 96 ± 148A1 and TnI 96 ± 148A7 are similar to that of TnI 96 ± 115 indicates that the interaction between the inhibitory region and TnC has not changed. As previously reported, it is believed that the inhibitory region interacts with the C domain of TnC (Cachia et al, 1983(Cachia et al, , 1986Chandra et al, 1994;Dalgarno et al, 1982;Drabikowski et al, 1985;Grabarek et al, 1981;Howarth et al, 1995;Jha et al, 1996;Kobayashi et al, 1994Kobayashi et al, , 1996Krudy et al, 1994;Lan et al, 1989;Leszyk et al, 1987Leszyk et al, , 1988Ngai et al, 1994;Slupsky et al, 1992;Swenson & Fredricksen, 1992;Tsuda et al, 1992;Wang et al, 1990;Weeks & Perry, 1978) and that the N domain, upon binding calcium, exposes a new hydrophobic surface area (Gagne et al, 1994(Gagne et al, , 1995Herzberg et al, 1986;. With the above results indicating that TnI residues 116 to 131 interact with TnC in a hydrophobic manner, these results strongly suggest that it is these residues that are interacting with the N domain of TnC.…”
mentioning
confidence: 79%
“…Since both domains of TnC interact with TnI, and in view of the sequence homology and similar 3D structures of TnC and CaM, it seems that the basic features of the complexes formed by these proteins may be similar. 'H-NMR (Campbell et al, 1991;Slupsky et al, 1992) and molecular modeling studies (Strynadka & James, 1990) suggest that this indeed is the case in so far as the hydrophobic pocket in each domain of TnC is the docking site for the segments of TnI. However, there are some important differences.…”
Section: Discussionmentioning
confidence: 95%